The effect of proposed educational units using problem-solving method in developing cognitive experience and learning the skill of passing and receiving in volleyball. Case study of 12 year old students in middle school - Bakri, Abdelkarim; louh, hicham (sports creativity, 2025)
This study aimed to find out the impact of the educational sessions of problem-solving in the realization and learning the skill ( pass, ready position) at volleyball, the case study of first year middle school students. The sample,40 students was divided for two groups, a controlling group was exposed to the traditional method, and an experimental group has undergone the problem-solving method. The data was collected through (Witkin)’s test (EFT ), After comparison of results of the experimental group, the findings showed that the educational sessions of problem-solving have more effective impact on the realization process and learning the basic skills than the traditional method under study